EVALUATION OF PERITONEAL-FLUID IN HORSES WITH EXPERIMENTAL ENDOTOXEMIA - Valadao, CAA; PEIRO, JR; Santana, A. E.; Bechara, G. H. (William E Jones Dvm, 1995)
Clinical parameters and biochemical and cellular changes in the plasma and peritoneal fluid were evaluated in horses after i.v. injection of a sub-lethal dose (50 ng/kg) of E. coli endotoxin. A significant decrease in the number of neutrophils and lymphocytes occurred in the blood 1h 15 min and 3 hours after injection of endotoxin; body temperature was increased significantly at the 3rd hour. No changes were detected in the total number of white blood cells in the peritoneal fluid. No significant differences in biochemical values were detected in either plasma or peritoneal fluid. Endotoxemia caused an alteration in blood cellularity, without effecting the peritoneal cellular population.